PENDEKATAN DALAM STUDI ISLAM - Shibghatullah, Firgha Abhista; Akbar Kusuma; Damanhuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The approach to Islamic studies is a way that seeks to make it easier for a person to know and understand Islam broadly and avoid the emergence of a superficial mindset. Islam seems to always spread its magnetic field for scholars, researchers, and practitioners to explore more deeply in its various aspects, in the study of Islam what is needed is not only a doctrinal approach, which in this case is termed by a philosophical theological approach, but also a scientific approach which according to him is divided into two, namely the historical linguistic approach and the anthropological sociological approach, The historical approach prioritizes the orientation of understanding or Interpretation of historical facts that act as a method of analysis, or knife of analysis, because history can present an overview of the elements that support the occurrence of an event, religion as the object of research must be explained its facts related to time. The psychological approach in Islam is useful for knowing and understanding how the level of religion that is understood, lived and practiced by a Muslim as well as being able to know the influence of prayer, fasting, zakat, hajj and other worships in a person's life. The philosophical approach in the study of religion seeks to find an explanation of the concept of religious teachings by examining and finding a system of reason that can be understood by humans.